Handbook of European employers' organisations - Mona Aranea; Philippe Demougin; Leon Gooberman; Marco Hauptmeier (Hans-Böckler-Stiftung, 2021)
This Handbook presents profiles of European Employers` Organisations (EEOs). The profiles provide general information on each organisation and detail how EEOs represent their member interests in the areas of employment relations, work, labour, and social policy in the European Union. This representation includes lobbying activities, joint work and relationships with labour unions and participation in EU institutions. This Handbook is aimed at practitioners and academics with an interest in the activities and impacts of EEOs, including unionists, employer representatives, policy makers and researchers of European employment relations and European Union integration.
Keywords: 330; Employers' Organisations; EEO; Lobbying; Employer representatives; Employment relations